Age, But Not Repeated Exposure to Gadoterate Meglumine, Is Associated With T1- and T2-Weighted Signal Intensity Changes in the Deep Brain Nuclei of Pediatric Patients. Issue 9 (September 2019) - Pozeg, Polona; Forget, Joachim; Meuli, Reto A.; Maeder, Philippe
Abstract : Objectives: Current findings on gadolinium deposition in the pediatric brain due to repeated exposure to macrocyclic contrast agents are inconclusive and possibly confounded by brain maturation processes. We evaluated the longitudinal effects of repeated gadoterate meglumine exposure (Dotarem; Guerbet, Villepinte, France) on the T1- and T2-weighted signal intensity (SI) in pediatric patients, and assessed the magnitude of age-related increase in T1-weighted (and decrease in T2-weighted) SI in a control cohort without prior gadolinium exposure. Materials and Methods: In this retrospective, double-cohort study, magnetic resonance imaging (MRI) data of 24 patients (0.7–16.4 years, M = 5.74, SD = 4.15) who received at least 10 doses of exclusively gadoterate meglumine were included in the longitudinal study. The MRI data of 190 controls (age range, 1–20 years; 10 patients/bin; bin width, 1 year) without any prior gadolinium-based contrast exposure were included in the control, cross-sectional study to assess the age-dependent SI changes in the regions of interest (ROIs). We measured SI (native), T1-weighted gradient echo, and T2-weighted fast spin-echo of 12 deep brain nuclei. The ROIs were measured at each of the first 11 MRI examinations of the contrast-exposed patients and in the control subject's MRI. Regions of interest's SIs, normalized by the pons, were analyzed with mixed effects models, accounting for the potential confounding factors, such as radiotherapy and chemotherapy. Results: The number of gadoterate meglumine administrations had no effect on the SI increase in any of the ROIs (all P > 0.05), but age significantly correlated with increased SI in T1-weighted globus pallidus (GP; P < 0.01) and caudate ( P < 0.05), and with decreased SI in T2-weighted GP ( P < 0.001) and dentate nucleus ( P < 0.005) in the contrast-exposed group. The cross-sectional analyses of the control cohort showed a significant age-dependent T1-weighted SI increase in multiple ROIs, including the GP and caudate, and decrease in the T2-weighted GP and dentate nucleus ( P < 0.05). Conclusions: Repeated exposure to gadoterate meglumine was not associated with brain hyperintensity in the pediatric patients, whereas age importantly contributed to the SI changes in several deep brain nuclei.